ANALISIS EFEKTIVITAS TEKNIK PERMAINAN PADA PEMAIN ELIT ATLET TENIS DUNIA - ramadhan, febrianto bagus; Pudjijuniarto, Pudjijuniarto Pudjijuniarto (Jurnal Kesehatan Olahraga, 2019)
One of the important elements in tennis is punch, especially punches that bounce to the ground or commonly known as groundstrokes. The purpose of this study was to analyze the percentage of the success rate on the effectiveness of field tennis blows in world elite tennis athletes and punches that contributed a lot of points. This research used quantitative method by using descriptive quantitative approach. Data sources in this study was taken by video footage of Rafael Nadal's men's singles tennis match in the open final of French 2010, Roger Federer in the final of Wimbledon 2017  and Grigor Dimitrov in the open last eight of Australia 2017. Based on the results of this study it can be concluded that the majority of Rafael Nadal and Roger Federer was crosscourt service 1 (first) with a success rate of 17.29% by Rafael Nadal and 26.50% by Roger Federer. While Grigor Dimitrov mostly crosscourt forehand with a percentage of 22.07%. While the majority of the error blows other than punch service by Rafael Nadal's players was forced error over baseline with a percentage of 46.94%, for Roger Federer and Grigor Dimitrov was unforced error over baseline with the percentage of 36.96% by Roger Federer and 28.85% by Grigor Dimitrov. While for service errors of Rafael Nadal, Roger Federer and Grigor Dimitrov, the majority of service errors in error over baseline with the percentage of 57.14% by Rafael Nadal, 58.82% by Roger Federer  and 54.29% by Grigor Dimitrov. Next for the win point, it was known that the majority of the blows that contributed a lot of win points to Rafael Nadal and Roger Federer was crosscourt (first) service 1, Rafael Nadal was 20 times with percentage of 20% and Roger Federer was 29 times with a percentage of 30.85% , while for Grigor Dimitrov was a crosscourt forehand punch 25 times with a percentage of 23.36%.Keywords: groundstroke, success analysis, and win point.